2018
DOI: 10.1186/s13643-018-0863-x
|View full text |Cite|
|
Sign up to set email alerts
|

Anesthesia interventions that alter perioperative mortality: a scoping review

Abstract: BackgroundWith over 230 million surgical procedures performed annually worldwide, better application of evidence in anesthesia and perioperative medicine may reduce widespread variation in clinical practice and improve patient care. However, a comprehensive summary of the complete available evidence has yet to be conducted. This scoping review aims to map the existing literature investigating perioperative anesthesia interventions and their potential impact on patient mortality, to inform future knowledge tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 73 publications
(64 reference statements)
1
7
0
Order By: Relevance
“…A final possible limitation is that relevant studies may have not been included, despite conducting a rigorous and standardized search of the literature [ 28 ]. If mortality terms were not mentioned in the title or abstract of a study, they would not have been included due to the literature search and screening process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A final possible limitation is that relevant studies may have not been included, despite conducting a rigorous and standardized search of the literature [ 28 ]. If mortality terms were not mentioned in the title or abstract of a study, they would not have been included due to the literature search and screening process.…”
Section: Discussionmentioning
confidence: 99%
“…This study conducted a cross-sectional secondary analysis of the original data set of 369 RCTs from our previously completed scoping review of anesthesia-related interventions that impact surgical patient mortality [ 28 ]. Details can be found elsewhere [ 28 ], in supplementary data. In brief, RCTs were retrieved from the following electronic databases: MEDLINE, Embase, CINAHL, CENTRAL, and the Cochrane Database of Systematic Reviews.…”
Section: Methodsmentioning
confidence: 99%
“…This systematic review will allow for identification, appraisal and summary of literature devoted to the guidance of intraoperative allogenic RBC transfusion. The Perioperative Anesthesia Clinical Trials Group (PACT) identified transfusion as one of seven themes that has a significant impact on mortality, reinforcing the importance of this review 60. The results of this review will provide rationale and justification for development of guidance or the need for prospective evaluation of various intraoperative transfusion strategies.…”
Section: Discussionmentioning
confidence: 83%
“…In the original publication of this article [ 1 ], Cole Etherington’s name was incorrectly captured as Nicole Etherington. The original article has been corrected.…”
mentioning
confidence: 99%